Population pharmacokinetics of a new long‐acting recombinant coagulation factor IX albumin fusion protein for patients with severe hemophilia B. (3rd October 2016) - Zhang, Y.; Roberts, J.; Bensen‐Kennedy, D.; Jacobs, I.; Santagostino, E.; Voigt, C.; Feussner, A.; Morfini, M.; Sidhu, J.
Abstract : Essentials The new recombinant factor IX (FIX) albumin fusion protein (rIX‐FP) has a prolonged half‐life. A population pharmacokinetic (PK) model was based on FIX activity levels of hemophilia B patients. The model was used to simulate different dosing scenarios of rIX‐FP to help guide dosing. The population PK model supported prolonged dosing of rIX‐FP with intervals of up to 2 weeks. Click to hear Prof.Makris's presentation on new treatments in hemophilia Summary: Background: The recombinant fusion protein linking recombinant coagulation factor IX with recombinant albumin (rIX‐FP; Idelvion ® ) exhibits a longer half‐life than plasma‐derived factor IX (FIX) and the commercially available recombinant FIX products. Objectives: (i) Characterize the population pharmacokinetics (PK) of rIX‐FP in hemophilia B patients, (ii) identify covariates that are potential determinants of rIX‐FP PK variability and (iii) simulate different dosing scenarios of rIX‐FP following single and steady‐state dosing. Patients/Methods: A population PK model was developed based on FIX activity levels of 104 patients who had received treatment with rIX‐FP. Patients were aged 1–65 years with FIX activity ≤ 2 IU dL −1 . PK sampling was performed for up to 14 days (336 h). Results: Simulation of a single intravenous infusion of rIX‐FP (25–75 IU kg −1 ) predicted that the median trough exogenous FIX activity levels would remain > 5 IU dL −1 for up to 16 days in adolescents/adults aged ≥ 12 years, up to 12 days in children aged 6 to < 12 years, and up to 9.5 days in children aged < 6 years. For steady‐state dosing, the median trough exogenous FIX activity levels were maintained at > 5 IU dL −1 for the duration of the dosing interval for the 25, 35 and 40 IU kg −1 weekly regimens and for 75 IU kg −1 every 14 days in adolescents/adults, and for the 35 and 40 IU kg −1 weekly regimens in children. Conclusion: The population PK model developed here correlates well with observed clinical data and supports prolonged dosing of rIX‐FP with intervals of up to 2 weeks.